Caracterização de esponjas nanoestruturadas de quitosana e policaprolactona para hemostasia - Fonseca, Alessandra Gabriela Leonel (2016)
Introduction: Regenerative medicine has analyzed biological effects of natural polymers, as an attempt to create materials which can be used for tissue repair purposes, such as hemostasis. Among these materials we can highlight the chitosan that has been studied because of its hemostatic property. Objective: This study aimed to characterize sponges made of chitosan (CS) and polycaprolactone (PCL) blends for possible use as a topical hemostatic agent. Material e Methods: Chitosan solutions were prepared in 1% acetic acid and PCL in acetone. These were associated in the following volumetric proportions (v/v): 100:0; 75:25; 50:50; 25:75; 0:100, then they were frozen at -80°C and lyophilized to form the sponges by a freeze-drying method. The samples were subjected to characterizations of Scanning Electron Microscopy (SEM), Fourier transform infrared spectroscopy (FTIR). It was held also an assessment of the interaction between sponges and blood tissue through the hemagglutination assay. Results: It was possible to observe the formation of chitosan sponges (CS) and CS/PCL, while when the solution of the pure PCL was used, it was observed that there was no sponge formation. The FTIR spectra revealed that there were no significant changes in the characteristic frequency of the functional groups when analyzed CS/PCL sponges when compared to spectra of pure polymers. The positive aspect hemagglutination was observed in the wells containing the pure chitosan sponges and CS75/PCL25. The hemolysis values were CS: 12.7%; CS50/PCL50: 9.6%; CS75/PCL25: 23.2%; CS25/PCL75: 6.5% e PCL: 3.52%. Conclusion: The blends of CS/PCL developed in this study were able to form sponges which showed intermediate chemical-physical characteristics between the materials, as well as hemagglutinating capacity, thus constituting a feasible alternative topical hemostatic agent for biomedical use.